Bismuth Borate Glass Based Nuclear Materials - Ghanem, A. H.; Farag, A. T. M.; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed; Farooq, W. A.; Yakuphanoğlu, Fahrettin (Springer, 2018)
A study of optical and gamma rays shielding properties was performed in the glassy system of (70-x)%B2O3-x%Bi2O3-15%ZnO-15%Na2O where x = 5, 10, 15, 20, 25. The samples were prepared by the melt quenching technique. The amorphous nature of the glass samples was proved using x-ray diffraction. The optical absorption spectra were obtained and the band gap was estimated. The effect of bismuth on the structural properties of the studied glasses was investigated through density rho and molar volume v(m). Optical band gap and Urbach energy were evaluated using optical data of UV-Visible measurements. The Gamma ray attenuation coefficient was measured at gamma ray energies 88.99, 302, 356.01, 661.64, 1173.23 and 1332.51 keV emitted from Cs-137 and Co-60 radioactive sources. The mass attenuation coefficient measurements show that the investigated system exhibits promising shielding properties.
Keywords: Urbach energy; Mass attenuation coefficient; Borate glass